Wesleyan Sanctification and the Ethic of Self‐Realization. (2nd December 2015) - Stromberg, Peter G.
Abstract: Among the related but distinct ideas that comprise contemporary American individualism is the ethic of self‐realization, the belief that each person has the moral duty to develop their own characteristic talents and potentialities. Here I argue that although the intellectual sources of this belief are well‐understood, we have little knowledge of how this idea became an ethic, how it acquired the emotional force of a moral directive. I suggest that this development can be explained in part by exploring the history of the Wesleyan doctrine of Sanctification, the conviction that the Christian believer can achieve a state of perfection. In the 19th century, debates erupted over whether Sanctification—originally an ecstatic experience occurring in revivals—could also take place as a gradual process, the development of Christian character. By the early 20th century, broader cultural forces conditioned a theological shift whereby Sanctification was increasingly understood in liberal thought as realization of the divinity that dwells within each individual soul. Along this path, Sanctification progressively permeated certain routines of daily life. This history provides an example of gradual transformation within Christianity, an example that can help to refine understandings of the processes of continuity and discontinuity that have been central to discussion in the Anthropology of Christianity.